Investigating the impacts of canine surgical sterilisation programmes for free-roaming dogs - Collinson, Abi (2023)
The majority of the global dog population is free-roaming. Efforts to manage these populations often include reproductive control using surgical sterilisation. Opinion regarding the effectiveness of such programmes is divided. Whilst advocates argue that they reduce or stabilise the population, improve dog welfare and contribute to canine-mediated disease control; detractors claim that their population level effects are unproven and that sterilised dogs can still have poor welfare, transmit disease, and cause conflict with humans and wildlife. A lack of impact assessment means that it is difficult to contribute meaningful data to the debate, and therefore problematic to make evidence-based decisions regarding their use.